2023
DOI: 10.20944/preprints202304.0153.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation of a PRD1-like Phage Uncovers the Carriage of Three Putative Conjugative Plasmids in Clinical Burkholderia Contaminans

Abstract: The Burkholderia cepacia complex (Bcc) are a group of increasingly multi-drug resistant opportunistic bacteria that can cause severe pulmonary infections. This resistance is driven through a combination of intrinsic factors and the carriage of a broad range of conjugative plasmids harbouring virulence determinants. Therefore, novel treatments are required to not only treat Bcc infection but also to prevent further spread of these virulence determinants. In the search for phages infective for two clinical Bcc i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…After screening various environmental samples, single plaques were produced on clinical isolate Burkholderia contaminans (strain 5080) ( 23 ) and another Bcc (strain 3726) from soil samples collected from Darwin, Australia. After purification and whole-genome sequencing, it was revealed that there was one distinct phage, CSP3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening various environmental samples, single plaques were produced on clinical isolate Burkholderia contaminans (strain 5080) ( 23 ) and another Bcc (strain 3726) from soil samples collected from Darwin, Australia. After purification and whole-genome sequencing, it was revealed that there was one distinct phage, CSP3.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we describe novel phage CSP3, isolated against two clinical isolates of Bcc organisms, one confirmed as Burkholderia contaminans ( 23 ). CSP3 is a new member of the Lessievirus genus, the first to be isolated from Australia.…”
Section: Introductionmentioning
confidence: 99%
“…are known hosts of IncP-type conjugative plasmids 31 we expect that the Burkholderia cenocepacia host used to isolate BCE1 carried such a plasmid (highlighting the serendipitous nature by which PDPs are often found) and we include BCE1 in our known plasmiddependent tectivirus phylogeny. Novel conjugative plasmids have recently been detected in Burkholderia contaminans isolates, after their existence was implicated by the isolation of alphatectiviruses on these strains 32 , suggesting Burkholderia species may be common hosts for these plasmids and phages. While the new plasmid-dependent tectiviruses we report greatly expand the known diversity of this group of phages, we found that all 51 phages in our collection had perfectly conserved gene synteny (Figure S1b).…”
Section: Incp Plasmid-dependent Tectiviruses From a Limited Geographi...mentioning
confidence: 99%